2018
DOI: 10.29252/beat-060108
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Brain CT-Scan Findings in Patients with Scalp Lacerations Following Mild Traumatic Brain Injury; A Cross-Sectional Study

Abstract: Objective: To determine the frequency of the brain CT-scan findings in patients with mild traumatic brain injury (TBI) and scalp lacerations. Methods: This cross-sectional study was conducted during a 1-year period from March 2016 to March 2017 in Level I trauma center in Shiraz, Southern Iran. We included all the adult patients (≥18 years) admitted to our emergency room with mild TBI (GCS on admission of 15) and scalp lacerations. All the patients underwent Brain CT-Scan and the scans were reviewed by two rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(29 reference statements)
3
2
0
Order By: Relevance
“…Our study identified another significant predictor that indicates the presence of intracranial injury, which was the presence of significant scalp wound, either laceration or contusion. This was consistent with past cross-sectional study of mild TBI patients, which concluded the association between scalp lacerations and intracranial injuries [13]. However, the detailed characteristics of the scalp wound to be associated with an increased risk was left undetermined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study identified another significant predictor that indicates the presence of intracranial injury, which was the presence of significant scalp wound, either laceration or contusion. This was consistent with past cross-sectional study of mild TBI patients, which concluded the association between scalp lacerations and intracranial injuries [13]. However, the detailed characteristics of the scalp wound to be associated with an increased risk was left undetermined.…”
Section: Discussionsupporting
confidence: 91%
“…We could not summarize from out data the definite characteristics of all the wounds, which were claimed to be significant, as they were not adequately documented. Based on a study by Hamrah et al and our clinical observation, we suggested that patients with mild TBI with large scalp laceration, which might be defined as the wounds with the width of �4 cm or the length of �7 cm, should be carefully evaluated as it can be associated with intracranial injuries in at least 20% of the patients [13]. However, these cutoffs were speculative, and further studies are still required to accurately define the wound's character that is significantly associated with an intracranial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained from studies conducted in Shiraz, Iran 33 and Basel, Switzerland. 13 Physical and psychological traumas caused by prior work-related injuries might affect sleep quality in negative ways.…”
Section: Discussionsupporting
confidence: 88%
“…This study also indicated that prior history of work‐related injury at the construction site was another risk factor for poor sleep quality. Similar results were obtained from studies conducted in Shiraz, Iran 33 and Basel, Switzerland 13 . Physical and psychological traumas caused by prior work‐related injuries might affect sleep quality in negative ways.…”
Section: Discussionsupporting
confidence: 79%
“…Scalp lacerations, hematomas, or other subcutaneous injuries are common in head trauma patients. Although isolated scalp injury is not often clinically significant, there is 20% association with intracranial injuries even in patients with mild TBI [24]. A visible scalp lesion on cross-sectional imaging directs attention to the site of impact for interpreting radiologists and assists in the detection of minor intracranial bleeds, fractures, or contusions [25].…”
Section: Scalp Lesionsmentioning
confidence: 99%